#TITLE_ALTERNATIVE# - BRAJAWIDAGDA (NIM: 23506003); Pembimbing: Dr. Oerip S. Santoso, M.Sc. dan Ir. Sri Purwanti, M.Sc, UUF
Job order, a production system which is usually applied by Small Medium Enterprise in manufacture area, is an order based production system. This production system characteristics are: small production batch, huge various products and short product life cycle. An order from customer must be responded quickly to meet the customer satisfaction. A quotation, consists of information about price and production time, is sent to customer as an order respond. In order to determine the price, a cost estimation process should be done quickly and accurately. Using K-Means and Multiple Linear Regression (MLR), an analogycal cost estimation approach is proposed in this thesis. The K-Means method is to create product clusters based on historical product while MLR is used to generate the estimation model for each cluster. The model accuracy is measured by Mean Absolute Percentage Error (MAPE) which reflects the model's capability.